Using microsoft office 97 - Kathy Ivens (Que, 1997)
Office 97: An integrated environment; Microsoft excel; Microsoft word; Microsoft access; Microsoft outlook; Microsoft powerpoint; Visual basic for applications; Microsoft publisher; Office 97 on the internet; Office 97 power user reference for windows 95...